Nuclear localization of Klotho in brain: an anti-aging protein - German, Dwight C. (2012)
Klotho is a putative age-suppressing gene whose over-expression in mice results in extension of life span. The klotho gene encodes a single-pass transmembrane protein whose extracellular domain is shed and released into blood, urine, and cerebrospinal fluid, potentially functioning as a humoral factor. The extracellular domain of Klotho has an activity that increases the expression of anti-oxidant enzymes and confers resistance to oxidative stress in cultured cells and in whole animals. The transmembrane form of the Klotho protein directly binds to multiple fibroblast growth factor receptors and modifies their ligand affinity and specificity. The purpose of the present study was to determine the precise cellular localization of Klotho in the mouse brain. Using light microscopic immunohistochemical methods, we found the highest levels of Klotho immunoreactivity in two brain regions: the choroid plexus, and cerebellar Purkinje cells. In the choroid plexus cells, Klotho was found not only on the plasma membrane but also in large amounts near the nuclear membrane. Likewise, in the Purkinje cell Klotho was found throughout the cell including dendrites, axon and soma with large amounts near the nuclear membrane. Using immunoelectron microscopy, we found Klotho in the cell membrane, but the highest concentration was localized in the peripheral portion of the nucleus and the nucleolus in both cell types. This new finding suggests that in addition to Klotho being secreted from cells in brain, it also has a nuclear function.